Research Progress on Molecular Mechanism of Moxibustion in the Treatment of Ankylosing Spondylitis - Yan, Min; Huali, Jiangshan; Wu, Linyun; Zhou, Xiao; Yang, Qing; Wu, Qinfeng; Liu, Xi; Wang, Hongyuan; Xu, Xiao (Chinese medicine and natural products, 2022)
As an important part of traditional Chinese medicine (TCM) nursing technology, moxibustion plays a unique role in improving the symptoms of ankylosing spondylitis (AS). The research on the mechanism of moxibustion intervention in AS mainly focuses on anti-inflammatory effects, immune regulation, bone metabolism regulation, intestinal flora regulation, and so on. Molecular medicine is of great significance to further clarify the mechanism of moxibustion intervention in AS. However, there are still some problems in the research on the molecular mechanism of moxibustion intervention in AS: the existing biomedical research methods only explore from a specific field and lack the exploration of moxibustion-targeted molecules based on biomedical network. In the future, the molecular network effect of moxibustion on AS can be discussed comprehensively and systematically with the help of omics technology and the construction of biological information interaction network between omics. The effect of moxibustion on upstream osteogenic transcription factors and related signaling pathways such as WNT, β-catenin, and BMP/Smads is not yet clear. Future research can focus on the relevant signal targets of bone reconstruction and clarify the mechanism of moxibustion against the new bone formation. In addition, there is a lack of research on the molecular mechanism of moxibustion in the treatment of AS from the perspective of metabolites. It is necessary to further explore the mechanism of moxibustion in the treatment of AS with the help of metabonomics technology.
Keywords: ankylosing spondylitis; moxibustion; molecular mechanism; anti-inflammatory; bone metabolism; intestinal flora